Addressing high processing temperatures in reactive melt infiltration for multiphase ceramic composites. Issue 2 (February 2023) - Makurunje, Phylis; Middleburgh, Simon C.; Lee, William E.
Abstract: Approaches for addressing the high processing temperatures required in reactive melt infiltration (RMI) processing of state-of-the-art multiphase ceramic matrix composites (CMCs) are reviewed. Ultra-high temperature ceramic composites can be realised by reactive melt infiltration of silicon, transition metals and/or alloys designed as immiscible phases, miscible phases, silicide phases and/or silicide eutectics to lower the temperature required for RMI. Whether carbides, borides or nitrides are envisaged in the resultant ceramic matrix composite, RMI presents an optimization challenge of balancing the composition of the phases incorporated and the processing temperature to be used. Current efforts aim at preparing complex and homogeneous microstructure preforms prior to RMI, minimising damage to reinforcing phases, applying rapid heating techniques, and developing in situ real-time monitoring systems during RMI. Future opportunities include integration of additive manufacturing and RMI, the increased use of process modelling and the application of in situ alongside in operando characterization techniques.